2020
DOI: 10.3390/ijerph17176424
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception of Air Pollution: A Systematic Review Focused on Particulate Matter Exposure

Abstract: The adverse health effects of exposure to air pollutants, notably to particulate matter (PM), are well-known, as well as the association with measured or estimated concentration levels. The role of perception can be relevant in exploring effects and pollution control actions. The purpose of this study was to explore studies that analyse people’s perception, together with the measurement of air pollution, in order to elucidate the relationship between them. We conducted a systematic review in accordance with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 85 publications
3
45
0
1
Order By: Relevance
“…Overall, our results show no direct evidence of a relationship between the implementation of the lockdown measures and the reduction of particulate matter in urban centers, except heavy traffic areas. Further research is needed to clarify this relationship, and it would also be interesting to examine the citizens' risk perception of air pollution in the context of the current Covid-19 emergency [25].…”
Section: Particulate Mattermentioning
confidence: 99%
“…Overall, our results show no direct evidence of a relationship between the implementation of the lockdown measures and the reduction of particulate matter in urban centers, except heavy traffic areas. Further research is needed to clarify this relationship, and it would also be interesting to examine the citizens' risk perception of air pollution in the context of the current Covid-19 emergency [25].…”
Section: Particulate Mattermentioning
confidence: 99%
“…Air pollution is a major environmental threat to public health worldwide [ 1 , 2 ]. The World Health Organization (WHO, Geneva, Switzerland) Air Quality Guidelines confirmed that over 4 million premature deaths were probably caused by particulate matter (PM)2.5 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…While we realize that actual measurements are preferable to a proxy such as reported traffic, we feel that such reports, especially used in conjunction with reports of the built environment, do provide useful information. A 2020 systematic review on the risk perception of air pollution reported that 31 out of 38 articles established a relationship between perception and measured pollution, even with variety of methodologies and population samples [ 97 ]. Clinicians should look closely at the contribution of an environmental factor such as traffic-related air pollution among patients who experience asthma/asthma-like symptoms to prevent deteriorating health.…”
Section: Discussionmentioning
confidence: 99%